2022
DOI: 10.3390/ijerph192316295
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Women’s Views of Pharmacist-Delivered Perinatal Depression Screening: A Qualitative Study

Abstract: Internationally, 20% of women experience perinatal depression (PND). Healthcare providers including general practitioners and midwives are critical in providing PND screening and support; however, the current workforce is unable to meet growing demands for PND care. As accessible and trusted primary healthcare professionals, pharmacists could provide PND care to complement existing services, thereby contributing to early detection and intervention. This study aimed to explore perinatal women’s views of communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Research on healthcare professionals’ perspectives on pharmacist-delivered screening is limited; however, available research demonstrates that generally other healthcare professionals are accepting of pharmacist-delivered screening for a range of medical conditions and risk factors [ 9 ]. Furthermore, perinatal women have also indicated that pharmacist-delivered PND screening and care could be beneficial [ 16 ]. There has been a shift to community-based primary care for many mental illnesses, resulting in many services and supports now being available through community pharmacies, including clozapine dispensing [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on healthcare professionals’ perspectives on pharmacist-delivered screening is limited; however, available research demonstrates that generally other healthcare professionals are accepting of pharmacist-delivered screening for a range of medical conditions and risk factors [ 9 ]. Furthermore, perinatal women have also indicated that pharmacist-delivered PND screening and care could be beneficial [ 16 ]. There has been a shift to community-based primary care for many mental illnesses, resulting in many services and supports now being available through community pharmacies, including clozapine dispensing [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that pharmacists are willing to take on roles in perinatal mental healthcare [ 13 ], with measurement instruments exploring pharmacists’ knowledge and attitudes in this area having been developed [ 14 , 15 ]. Recent evidence from interviews with perinatal women in Australia demonstrates that they are also generally accepting of pharmacists’ roles in this area if pharmacists had appropriate training [ 16 ]. Examining pharmacists’ perspectives of PND screening, specifically, is necessary to inform the development of such a service in an acceptable manner [ 6 ].…”
Section: Introductionmentioning
confidence: 99%